2012
DOI: 10.1038/jhh.2011.113
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory markers are associated with left ventricular hypertrophy and diastolic dysfunction in a population-based sample of elderly men and women

Abstract: Markers of inflammation have previously been related to left ventricular (LV) hypertrophy (LVH) in uremic and hypertensive patients. The present study investigated inflammatory markers in relation to LV geometry and diastolic function in a population of elderly persons. In the population-based Prospective Study of the Vasculature in Uppsala Seniors (PIVUS) study (1016 men and women 70 years of age), echocardiograms to determine relative wall thickness (RWT), LV mass index (LVMI) and the E/A-ratio were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 31 publications
3
40
0
7
Order By: Relevance
“…Masiha et al . reported that inflammatory markers such as high-sensitivity c –reactive protein (hsCRP), ICAM-1, and VCAM-1 were elevated in concentric LVH, and hsCRP was correlated with LV diastolic function, while inflammation might play a pathogenetic role in abnormal LV geometry and function20. On the other hand, Angpt2 is associated with pro-inflammatory responses with P-selectin, E-selectin and VCAM-112.…”
Section: Discussionmentioning
confidence: 99%
“…Masiha et al . reported that inflammatory markers such as high-sensitivity c –reactive protein (hsCRP), ICAM-1, and VCAM-1 were elevated in concentric LVH, and hsCRP was correlated with LV diastolic function, while inflammation might play a pathogenetic role in abnormal LV geometry and function20. On the other hand, Angpt2 is associated with pro-inflammatory responses with P-selectin, E-selectin and VCAM-112.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, inflammatory markers and endothelial activation molecules were found to be associated with LV hypertrophy and diastolic dysfunction in a population-based sample of elderly men and women [11]. We can hypothesize that inflammation that leads to endothelial activation triggers the cardiac fibrosis; therefore, it can play an important role in diastolic dysfunction.…”
Section: Lvmimentioning
confidence: 93%
“…Recently, both LV hypertrophy and diastolic dysfunction have been found to be associated with systemic inflammation in obese and hypertensive adults [10,11]. This association might be mediated by clinical risk factors that are themselves related to an inflammatory state.…”
Section: Introductionmentioning
confidence: 99%
“…Ten out of 13 studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]26] included normotensive controls in their series and all but one study [27] showed a significant increase in right ventricular wall thickness in hypertensive patients as compared to their normotensive counterparts. Fig.…”
Section: Comparison Between Hypertensive Patients and Normotensive Comentioning
confidence: 99%
“…Moreover, elevated left ventricular pressure due to diastolic dysfunction in hypertrophied hearts is an important mechanism leading to venous pulmonary hypertension and to right ventricular pressure overload [12,13]. Finally, left ventricular hypertrophic adaptation to systemic hypertension is multifactorial being sustained by a number of growth factors including aldosterone, catecholamines, angiotensin, insulin, cytokines and inflammatory markers [14,15]. All these circulating or locally produced substances may be responsible of the hypertrophic response of the right ventricular independently of haemodynamic alterations of the pulmonary circulation.…”
Section: Introductionmentioning
confidence: 99%